Numerical simulation on magnetic assembled structures of iron-based metallic particles within MMCs by a homogeneous strong magnetic field. (17th August 2015) - Liu, Chunwei; Sun, Zhi; Zheng, Lichun; Huang, Shuigen; Blanpain, Bart; Guo, Muxing
Abstract: Particle-reinforced metal matrix composites (MMCs) have excellent physicochemical properties as structural materials. The morphology and distribution control of reinforcement particles during the fabrication of MMCs are difficult-but-critical-to-achieve required properties of the materials. This research demonstrates a possibility to quantitatively control the distribution of particles in the metal matrix by applying a magnetic field. A 2D numerical model is developed and applied to evaluate the behaviour of Fe-based metallic particles in aluminum MMCs. By combination of 2D simulation with intersectional directions, this model also provides some hints for 3D practice. The assembled structure is found to be governed by the external magnetic field orientation, magnetic flux density and magnetic susceptibility of the particles. Both behaviours of particle agglomeration and dispersion are quantitatively characterized in different conditions. By using a strong magnetic field, it is found that assembled structures of weakly magnetic particles can be effectively manipulated. Therefore, it can be expected to fabricate particle-enhanced metal matrix composites/ceramics/glass with substantial improvements in physical and chemical properties by using a magnetic field.